Initial Experience With the NICO Myriad Device for Minimally Invasive Endoscopic Evacuation of Intracerebral Hemorrhage. Issue 3 (11th September 2022) - Song, Rui; Ali, Muhammad; Smith, Colton; Jankowitz, Brian; Hom, Danny; Mocco, J; Kellner, Christopher P.
Abstract : BACKGROUND: Intracerebral hemorrhage (ICH) is a devastating form of stroke for which there is no consensus treatment. Although open craniotomy has been explored as a surgical treatment option, multiple minimally invasive (MIS) techniques have been developed including endoscopic evacuation. An adjunctive aspiration device can be used through the working channel to provide an additional degree of freedom and increased functionality regarding clot manipulation and morcellation. OBJECTIVE: To report our single-center technical experience with the Myriad device used as an adjunctive aspiration device during endoscopic ICH evacuation in an exploratory case series. METHODS: Demographic, clinical, and radiographic data were collected on patients who underwent MIS endoscopic ICH evacuation using the Myriad aspiration device from December 2018 to March 2019. RESULTS: Eight patients underwent ICH evacuation with the Myriad aspiration device. Bleeding was confined to the cortex in 4 patients, subcortical region in 2 patients, and the cerebellum in 2 patients. One of the cerebellar cases also underwent suboccipital craniotomy. The mean preoperative hematoma volume was 65.1 ± 68.9 mL, and the median postoperative volume was 7.6 ± 9.0 mL, for an average evacuation percentage of 88.1% ± 12.1%. In 75% of the cases, a bleeding vessel was identified and treated with either cautery or irrigation alone. There was no hemorrhagic recurrence or mortality within 30 days. CONCLUSION: Data from this initial experience suggest that MIS endoscopic ICH evacuation with the NICO Myriad aspiration device is feasible and technically effective. Multicenter exposure is necessary to verify broader applicability.